2015
DOI: 10.1016/j.neuro.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of exposure to organophosphates and pyrethroid pesticides among Thai children

Abstract: The use of pesticides for crop production has grown rapidly in Thailand during the last decade, resulting in significantly greater potential for exposure among children living on farms. Although some previous studies assessed exposures to pesticides in this population, no studies have been conducted to evaluate corresponding health effects. Twenty-four children from a rice farming community (exposed) and 29 from an aquaculture (shrimp) community (control) completed the study. Participants completed a neurobeha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 40 publications
2
50
1
1
Order By: Relevance
“…In the same Ecuadorian population as our study, a pilot study also observed delays in children's reaction time among children with concurrent pesticide exposures (Grandjean et al, 2006). Contrasting with our findings, a pilot study of children found no effect of pesticide application seasons on neurobehavioral performance (Fiedler et al, 2015). The lack of association may have occurred due to its small sample size (n=53).…”
Section: Discussioncontrasting
confidence: 99%
“…In the same Ecuadorian population as our study, a pilot study also observed delays in children's reaction time among children with concurrent pesticide exposures (Grandjean et al, 2006). Contrasting with our findings, a pilot study of children found no effect of pesticide application seasons on neurobehavioral performance (Fiedler et al, 2015). The lack of association may have occurred due to its small sample size (n=53).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, average 3-PBA concentrations across seasons and the within-person change in 3-PBA concentrations across seasons were not associated with measures of neurobehavioral function (Fiedler et al 2015). Two large cross-sectional studies of pyrethroid exposure and neurobehavioral outcomes in children aged 6–15 years did not report a significant relationship between 3-PBA and neurobehavior (Oulhote and Bouchard 2013; Quiros-Alcala et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…However, exposure to OPs rarely occurs in isolation and is often a complex mixture of OPs and other pesticides [13]. A study examining the neurobehavioral effects of OPs and pyrethroids, a different pesticide class, found no significant adverse neurobehavioral effects in Thai children [119]. Likewise, OPs and pyrethroids were found to have opposing effects in infants [120].…”
Section: Discussionmentioning
confidence: 99%